Improving Mobile Value-Added Services (MVAS) in Yemen Mobile Companies - Hajar, Mohamed A.; Daing Nasir, Ibrahim; Mohd Ridzuan, Darun; Al-Sharaﬁ, Mohammed A. (IJITLS, UAE, 2020)
Mobile Value-Added Services (MVAS) is a general expression for any services added to mobile phone networks other than voice services. However, the difficulty of identifying and promoting the appeal MVAS to the individual customer is vague and often confusing. This empirical study aims to reduce this vague by assisting service providers in targeting the right customer with the right services. The purpose of this paper is to propose guidelines to efficiently improve the value-added services of Mobile Companies in Yemen through the promotion of customer satisfaction and loyalty. Accordingly, a questionnaire survey was conducted, and data were collected over 1000 mobile users in the Republic of Yemen. Also, market observations were undertaken to define difficulties and limitations. The results showed that MVAS has positive effects on customer satisfaction and loyalty, and hence on company’s performance and profitability. Finally, the study provides some recommendations to improve MVAS in Yemen telecommunications companies.